Islam and Politics: Separation or Collaboration of Religion and State - Mina Manjurul Hossain Reza (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
There has long been discussion and controversy about the relationship between Islam and politics, particularly in respect to the idea of separating religion and state. Religion has always been entwined with law and government in many Islamic societies. However, in countries with a majority of Muslims, the concept of keeping religion and the state apart, which is prevalent in many secular countries, has different meanings and uses. There are political systems in certain nations with a majority of Muslims that include aspects of Islam and politics working together as well as working apart. In many nations and situations, politics and Islam are frequently entwined. Like many other religions, Islam has tenets that can affect governance and political structures. Argue that Islam provides a moral compass for governance, while others emphasize the importance of individual freedoms and secular governance. Based on articles, books, and the comprehensive arguments of some researchers, this paper showed the relationship between Islam and politics from the perspective of religion and state.